The moderating role of firm size in the relationship between financial performance and tax avoidance - Felicia Auryn; Galumbang Hutagalung; Enda Noviyanti Simorangkir; Sauh Hwee Teng (International Journal of Academe and Industry Research)
This study examines the influence of leverage, profitability, and profit growth on tax avoidance, with firm size as a moderating variable. Using a quantitative approach, the research analyzes sixteen health sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that leverage and profit growth do not significantly affect tax avoidance, while profitability has a positive and significant effect. Furthermore, firm size does not moderate the relationship between leverage, profitability, and profit growth on tax avoidance. These results highlight that internal financial indicators may influence tax avoidance behavior more directly than organizational scale. Beyond regulatory implications, the findings underscore the importance for firms to align financial performance with ethical tax practices, and for stakeholders to consider non-size-related factors when evaluating corporate tax behavior.